A review: soil properties mapping estimation using remote and proximal sensing data - Koumoulidis, Dimitrios; Efthimiadou, Aspasia; Katsenios, Nikos; Hadjimitsis, Diofantos G. (My University, 2024)
Soil is the life support system of terrestrial ecosystems, making comprehending its processes and functions vital for global food security, global climate change regulation, and achieving sustainability in agriculture. The knowledge of soil processes and the up-to-date soil status is a prerequisite towards sustainable environmental management and for reducing risks in decision-making. Over the past decades, the notable introduction and adoption of digital technologies in Remote Sensing (RS), the improvement of spatial data applications, the development of quantitative techniques to understand soil patterns, and the detailed visualization of soils through new applications, increased our capacity to predict, assess and explain soil and its patterns. The current review paper, apart from accessing techniques/applications of RS and Proximal Sensing (PS) utilized towards soil mapping predictions, extends its interest in demonstrating the increasingly key role of RS and PS utilized to determine soil attributes such as texture, soil moisture, soil organic carbon (SOC) and iron content. Limitations and the difficulties of remote and proximal sensing are overviewed, while additionally, the crucial issue of accuracy of the classification of the thematic maps derived is addressed. Furthermore, this review paper aims to review the status of current mapping methods and provide deeper and more detailed insight into techniques in contemporary systematic soil mapping.
Keywords: Soil mapping methods; Remote & Proximal Sensing; Soil variables prediction; Multivariate statistical techniques.